Attitudes toward food additives in Hungarian consumers - preliminary results - Tarnavölgyi, Gábor (Acta agriculturae slovenica. Suplement, 2004)
Consumer attitudes towards food additives were examined in a questionnaire survey. In our research it definitely shows up that consumers consider the use of food additives as rather dangerous. The main reason for this meaning is the unacquaintance: about half of the respondents could not even define either food additives or E-numbers. Consumers were also asked whether they were aware of the additive content of certain foods. Most people showed greater awareness on this issue than we expected, although we discovered some incredibly erroneous views, too. The consumers had various opinions of the technological necessity of additives, but most people think that some of these compounds are needlessly added to foods. The role of food additives in the decision process of the consumers is diverse: although most consumers do not care about this issue, many of them prefer products containing less additives among foods of same quality and price, and there are some who are willing to pay more for them. Vast majority of the interviewed people would support the introduction of an "additive-free food" mark.
Keywords: dodatki; Madžarska; potrošniki; prehrana; varnost živil; živila